TIME TRAVEL ESTIMATIONS USING MAC ADDRESSES OF BUS, PASSENGERS: A POINT TO PATH-QGIS ANALYSIS - Arief Hidayat; Shintaro Terabe; Hideki Yaginuma (Department of Urban and Regional Planning, Diponegoro University, 2018)
Currently, the developmentof wifi is proliferating. Especially in the field of transportation and smart cities. At the same time, wifi is a low-cost technology, which offers a longer survey time and is able to support the big data era. This paper describes our study, which first uses a wifi scanner to capture media access control (MAC) address data of bus passengers wifi devices and then identifies each MAC address travel time to confirm the bus passengers. The MAC address is a unique ID for aech device used suchh as moble phones, smartphones, laptops, tablets, and other wifi-enabled equipment. The wifi scanner was placed inside the bus to capture all tthe MAC addresses inside and around the bus. The survey was conducted for one day (eight hours). The paper describes the procedure of the time travel estimation for each MAC address using the “point to path” analysis in QGIS open source software. This procedure, using point to path-GIS, produced 70.000-80.000 raw data points cleaned into 100-130 new data point. The procedure determined how many passengers traveled and explained which bus passengers used based on travel time.